Insulin and Insulin Treatment - Rehan Naqvi (International Journal of Integrative Research, 2023)
Insulin is a potent anabolic hormone, and its absence induces a profound catabolic state that affects fat, carbohydrates, and protein stores. Absolute insulin deficiency, such as that characterized by type 1 diabetes (T1DM), results in death if left untreated. The study of patients with diabetes in the pre-insulin era teaches us the surprisingly long period that can survive without insulin. Leonard Thompson was the first patient to have an effective insulin treatment. He was 12 years old when he was diagnosed with diabetes in 1919 and had survived for over 2 years at 11 am on January 22, 1922; he received his first injection of insulin. This indicated that it was miserable without insulin. In addition to weight loss, constant tiredness, thirst, urination, and frequent infections, their waste was the e certain knowledge that a death sentence had been passed and that death would be an agonizing and slow process. The most effective therapy available at that time appeared to be a severe nutritional restriction, perhaps most popularly expounded by Allen [1] from the Rockefeller Institute in New York. However, this was a difficult regimen that did not appear to significantly prolong life expectancy when death occurred. It is not clear whether this was the result of diabetes or starvation.